2010
DOI: 10.1177/1076029610379849
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Outcome of 260 Pediatric ITP Patients in One Center

Abstract: In the current study, clinical and laboratory findings and treatment modalities of children with acute and chronic immune thrombocytopenic purpura (ITP) were evaluated retrospectively. Our purpose was to determine clinical outcome of children with ITP and their responses to different treatment regimes. Total of 260 children with ITP were enrolled in the study. The mean age of patients was 76.8 ± 48.1 months. The therapy responses of high-dose methylprednisolone (HDMP; n = 134), standard dose methylprednisolone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 36 publications
2
22
1
Order By: Relevance
“…Figure 5). 19,22,26,27,[30][31][32]37,44,46,[48][49][50] No significant differences were found. Fourteen studies analyzed the influence of treatment with IVIg and found significantly less chronic ITP in patients treated with IVIg (OR 0.71, 95% CI 0.52-0.97) ( Figure 5).…”
Section: 2334mentioning
confidence: 76%
See 4 more Smart Citations
“…Figure 5). 19,22,26,27,[30][31][32]37,44,46,[48][49][50] No significant differences were found. Fourteen studies analyzed the influence of treatment with IVIg and found significantly less chronic ITP in patients treated with IVIg (OR 0.71, 95% CI 0.52-0.97) ( Figure 5).…”
Section: 2334mentioning
confidence: 76%
“…18,22,30,31 Three studies found significant less chronic ITP in patients with mucosal bleeding (OR 0.39; 95% CI 0.28-0.54).…”
Section: Clinical Predictorsmentioning
confidence: 99%
See 3 more Smart Citations